APPLAYING TELL AND SHOW STRATEGY ON WRITTENT TEXT OF YOUNG LEARNERS - suhono suhono; Yeasy Agustina Sari (State Institute for Islamic Studies IAIN of Metro, 2018)
The aim of this research was to know whether of applying Tell and Show strategy can influence learners’ descriptive text at the Tenth grade of English Course Surakarta. The researchers used true experimental design which consist of control groupand experimental group.The subject of this research was students of young learner at the tenth grade of English Course at Surakarta. This research was quantitative research design in the form of experimental research. The researcher uses test as the data collection method. To investigate whether there was a positive and significant differences study between experimental class and control class. The researcher analyzed the data by using t-test formula. The result revealed that the average score of Experiment class was higher (72.12) than the average of control class (66.23). It can be concluded that teaching in the experimental class using Tell and Show (TS) strategy gave better result than in the control class using the other strategy in teaching descriptive text. the result of data analysis using t-test is t-observed = 5.289 and t-table = 5% : 2.000, 1% : 2.660. It means that t-observed is higher than t-table = 5.289 > 2.000. It can be inferred that Ha is accepted and Ho is rejected.It can be concluded that is using Tell and Show (TS) strategy gave more positive effect toward the learnerners’ descriptive text writing ability.